Media Within Psycholinguistic and Media Psychological Context - Machikova, Maria (East European Journal of Psycholinguistics, 2015)
The article substantiates the necessity to study the media space within interdisciplinary paradigm, i.e. at the intersection of psycholinguistics and mediapsychology which are focused on so-called “man-sized systems” (in other words – media-discourses that are capable to change the world view of both an individual and a nation). Thus discourse-analysis is regarded as a leading interdisciplinary research method of media space. Psycholinguistics and mediapsychology approaches unity to the study of modern media is determined by the proximity of their paradigmatic organization: a) these disciplines are marginal so they expand the boundaries of traditional psychology, linguistics, communication science; b) psycholinguistics and mediapsychology are considered as the newest branches of psychological science, their subject is a  person in the context of interaction of language and mental factors (psycholinguistics) or modern media culture (mediapsychology); c) text and discourse are defined as the main manifestations of a person and tools of influence on him/her. Discourse-analysis of a media space should be based on  media – hypermedia – transmedia paradigm  and should be explored through the lens of a convergent approach. Convergence promotes global changes in media sphere leading to the emergence of a new (converged) media, namely: social networks (VKontakte, Facebook, etc.), Internet TV platforms (ITV), microblogging (Twitter). Among the tasks that psycholinguistics and mediapsychology are able to solve jointly there are the following: the study of individual behavior, caused by the influence of individual and mass communications means; the study of communicative behavior of an  individual in the context of the media influences and within the system of media texts of different genres; the study of personal and group media effects; the analysis of the impact of media environment through the prism of speech on the development of  an individual,  achievement of a personhood and his/her psychological well-being. The marginal object of the research (transmedia) requires the appropriate marginality of approaches. The organization of media space will eventually become more complex, so the general methodological principles of modern science such as  expansionism, anthropocentrism, ecsplanatoriness and functionalism will become crucial.ReferencesАnanyev, B. (2009). Lyduna yak pisnanna [Human as Cognition]. Retrieved fromhttp://psm.in.ua/index-59.html.Beaugrande, R. de. (1997). New Foundations for a Science of Text and Discourse.Greenwich, CT: Ablex.Ivanov, V., Voloshenyk, O. (2014). Mediapsuhologiya. Mediagramotnist[Mediapsychology. Mediaiteracy]. Kyiv: Taras Shevchenko National University of Kyiv.Kalmykov, A. (2011). Professionalnaya Universalisaciya i Specialisciya KonvergentnihSMI [Professional Universalization and Specialization of Converged Media]. Retrieved07.03.2015 from http://jarki.ru/wpress/2011/01/28/1792Manovich, L. (2001). The Language of New Media. Cambridge, Massachusetts: TheMIT Press,Matveyeva, L. (2011). Aktualnye problemy mediapsychologii [Actual problems ofmediapsychology] (pp. 151–168). In: Chelovek kak obyekt i subyekt mediapsychologii [Human asSubject and Object of Mediapsychology]. Мoscow: Moscow State University.Naydenova, L. A. (2014) Medaipsihologiya: Osnovy Reflexivnoho Pidhodu[Metapsychology: Bases of Reflective Approach]. Kyiv: Taras Shevchenko National University ofKyiv.Phillips, L., Yorgensen, V., (2008). Diskurs-Analis. Teoriya i Praktika [DiscourseAnalysis: Theory and Practice]. Kharkiv: Humanitarnyi Centr.Pronina, Е. (2001). Kategorii Mediapsychologii [Categories of Mediapsychology].Retrieved 07.03.2015 from http://evartist.narod.ru/ text7/38.Ryasantseva, T. (2010). Gipertext i Elektronnaya Kommunikaciya [Hypertext andelectronic communication]. Мoscow: Liki.Stepanov,Y. (1999). Paris-Moscow, vesnoy i utrom… [Paris - Moscow in the Spring andin the Morning ...] (pp. 3–11). In: Kvadratura smisla: Francusckaya shkola diskurs-analisa [AreaSense: French School of Discourse Analysis]. Мoscow: ProgressStyopin, V. (2003). Samorasvivayshiesa sistemi i postneklassicheskaya racionalnost[Selfdeveloping system and postnonclassical rationality], Voprosy Philosophii, 8, 5-17.Herring, S. C. (2011). Commentary: Contextualizing digital discourse. In: Digitaldiscourse: Language in the new media. C. Thurlow & K. Mroczek, (eds.), New York: OxfordUniversity Press.Winterhoff-Shpurk, P. (2007). Mediapsychology. Basic principle. Kharkiv:Humanitarian Centre.Q&A with Director of the Media Psychology Research Center, Pamela Rutledge Phd,MBA. (2014). Retrieved from http://www.onlinepsychologydegrees.com/interview/pam-rutledge.Yates, S. T. (1996). Oral and written linguistics aspects of computer conferencing: Acorpus based study (pp. 29–46). In: Communication: Linguistic, Social and Cross-CulturalPerspective. Amsterdam: John Benjamins Publishing, 1996.